Simulation of the hybrid Tunka Advanced International Gamma-ray and Cosmic ray Astrophysics (TAIGA) ... - Kunnas, M; Astapov, I; Barbashina, N; Beregnev, S; Bogdanov, A; Bogorodskii, D; Boreyko, V; Brückner, M; Budnev, N; Chiavassa, A; Chvalaev, O; Dyachok, A; et al. (Humboldt-Universität zu Berlin, 2015)
Up to several 10s of TeV, Imaging Air Cherenkov Telescopes (IACTs) have proven to be the instruments of choice for GeV/TeV gamma-ray astronomy due to their good reconstrucion quality and gamma-hadron separation power. However, sensitive observations at and above 100 TeV require very large effective areas (10 km2 and more), which is difficult and expensive to achieve. The alternative to IACTs are shower front sampling arrays (non-imaging technique or timing-arrays) with a large area and a wide field of view. Such experiments provide good core position, energy and angular resolution, but only poor gamma-hadron separation. Combining both experimental approaches, using the strengths of both techniques, could optimize the sensitivity to the highest energies. The TAIGA project plans to combine the non-imaging HiSCORE [8] array with small (∼10m2) imaging telescopes. This paper covers simulation results of this hybrid approach. ...